A new porcupine (Rodentia, Hystricognathi, Erethizontidae) from the Early and Middle Miocene of Patagonia (Ameghiniana, 2013)
Abstract. A new erethizontid, Branisamyopsis australisgen. et sp. nov., from Colhuehuapian sediments (early Miocene) of the Sarmiento Formation cropping out at Gran Barranca, Chubut Province, Argentina, is described. The new genus is also identified in the middle Miocene (Collón Cura Formation) at Cañadón del Tordillo (Neuquén, Argentina). The comparative study of the mandibular and tooth morphology of erethizontids indicates that Branisamyopsis australisgen. et sp. nov. is closely related to Patagonian porcupines EosteiromysAmeghino and SteiromysAmeghino. Branisamyopsis australisgen. et sp. nov. shows that extinct erethizontids reached their greatest taxonomic diversity during the Colhuehuapian. The cheektooth morphology of Patagonian Colhuehuapian erethizontids could correspond to different dietary adaptations. The temporal and geographic distribution and the phylogenetic affinities of Branisamyopsis, Eosteiromysand Steiromyssuggest that Patagonia was a marginal area of differentiation for the family, unconnected with the radiation of living porcupines.Resumen. UN NUEVO PUERCO ESPÍN (RODENTIA, HYSTRICOGNATHI, ERETHIZONTIDAE) DEL MIOCENO TEMPRANO Y MEDIO DE PATAGONIA. Se describe un nuevo eretizóntido, Branisamyopsis australis gen. et sp. nov., proveniente de sedimentos colhuehuapenses (Mioceno temprano) de la Formación Sarmiento aflorante en Gran Barranca (Chubut, Argentina). El nuevo género se identifica también en el Mioceno medio (Formación Collón Cura) de Cañadón del Tordillo (Neuquén, Argentina). El estudio comparativo de la morfología mandibular y dentaria de los eretizóntidos indica que Branisamyopsis australis gen. et sp. nov. está cercanamente vinculada a los puerco espines patagónicos Eosteiromys Ameghino y Steiromys Ameghino. Branisamyopsis australisgen. et sp. nov. muestra que los eretizóntidos extintos alcanzaron su mayor diversidad taxonómica durante el Colhuehuapense. La morfología dentaria de los eretizóntidos patagónicos colhuehuapenses podría corresponder a diferentes adaptaciones dietarias. La distribución temporal y geográfica y las afinidades filogenéticas de Branisamyopsis, Eosteiromysy Steiromys sugieren que Patagonia sirvió como un área marginal de diferenciación para la familia no vinculada con la radiación de puerco espines vivientes.